Numerical Modelling for Optimization of Fibres Winding Process of Manufacturing Technology for the Non-Circular Aerospaces Frames - Petru, Michal; Mlynek, Jaroslav; Martinec, Tomas (Manufacturing Technology Journal, 2018)
This article deals with the issue of mathematical calculating the trajectory of the end-effector of an industrial robot in the manufacture of aerospace composites. Robots are used to define the winding orientation of the fibre strands on a non-bearing 3D core. The 3D core is attached to the robot-end-effector and is led through a fibre-processing head according to a suitably defined robot trajectory during winding of the fibre on the core. The quality of the composite depends greatly on the correct winding angles of the fibres on the frame and on the homogeneity of the individual winding layers. The implementation of these two conditions is related to determining the correct trajectory of the industrial robot, which is part of the composite production technology. The numerical modelling of a passage of the on-bearing 3D core through a fibre-processing head is described in the article. Differential evolution algorithm and matrix calculus are applied to the numerical calculation of optimized robot-end-effector trajectory to achieve optimal angles of windings of fibres on the frame. The numerical calculations of the trajectory of the robot-end-effector were used for verified for the calculated trajectory of the robot-end-effector in the real conditions of robotic laboratory of department of machinery construction.
Keywords: Numerical modelling; Optimization; Aerospace frame; Composite materials; Winding technology